2007
DOI: 10.1212/01.wnl.0000252822.53506.46
|View full text |Cite
|
Sign up to set email alerts
|

Familial effects on the clinical course of multiple sclerosis

Abstract: Familial factors do not significantly affect eventual disease severity. However, they increase the probability of a progressive clinical course, either from onset or after a phase of relapsing remitting disease. The familial effect is more likely to reflect genetic than environmental conditions. The results are relevant for counseling patients and have implications for the design of studies seeking to identify factors that influence the natural history of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 32 publications
4
45
1
4
Order By: Relevance
“…Twin studies demonstrate that concordance of disease course is higher in monozygotic twins when compared to dizygotic twins or siblings; 39 family studies in MS have reported similar results. 40 Although several clinical MS phenotypes have been pursued for genetic studies, one strategy is to compare individuals who are discordant for long-term outcomes. Here, we examined MS cases lying at opposite extremes of the distribution of long-term disability ('mild' and 'severe' disease subgroups) as defined previously.…”
Section: Discussionmentioning
confidence: 99%
“…Twin studies demonstrate that concordance of disease course is higher in monozygotic twins when compared to dizygotic twins or siblings; 39 family studies in MS have reported similar results. 40 Although several clinical MS phenotypes have been pursued for genetic studies, one strategy is to compare individuals who are discordant for long-term outcomes. Here, we examined MS cases lying at opposite extremes of the distribution of long-term disability ('mild' and 'severe' disease subgroups) as defined previously.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that either shared genetic or environmental factors, or both, in part determine which disease course an individual will experience. Perhaps the most challenging observation to the hypothesis that disease course is genetically determined is the observation that disease course was not transmitted from affected parents to offspring (Hensiek et al, 2007). Despite its relatively large size (1083 families) this study may not have had sufficient statistical power to discern transmission of weak genetic effects.…”
Section: Family Studiesmentioning
confidence: 95%
“…A larger European family-based study of 1083 families with two or more first-degree relatives with MS found concordance in disease course between affected siblings (kappa ¼ 0.12, p < 0.001) but, interestingly, not between parents and children (kappa ¼ -0.04, p ¼ 0.09) (Hensiek et al, 2007). Although interpreted as indicating a genetic influence on disease course, this observation argues more for an effect of shared sibling environment on disease course because disease course did not appear to be transmitted from parents to offspring.…”
Section: Family Studiesmentioning
confidence: 99%
“…[12][13][14] Most of the published studies so far have aimed at finding associations between DNA markers and MS susceptibility and very few studies have attempted to correlate disease clinical features with DNA variants. [14][15][16][17] A possible explanation is that it is usually difficult in practice and very expensive to collect both DNA and high-quality clinical information required for these studies on a large enough collection of patients. In France, through a national network REFGENSEP (Réseau Français d'Etude Génétique de la SEP), we have been able to collect the DNA of a large number of MS patients and their parents (651 case-parent trios).…”
Section: Introductionmentioning
confidence: 99%
“…It was 20 years [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] in the total group, 31 years [26][27][28][29][30][31][32] in the RR MS group, 14 years [10][11][12][13][14][15][16][17][18][19][20] in the SP MS group and 9 years [6][7][8][9][10][11][12][13][14][15][16][17] in the PP MS group ( Figure 1). As expected, these figures were significantly Figure 1 Median time to reach Expanded Disease Status Scale (EDSS) 6 for all patients and patients stratified according to MS type.…”
mentioning
confidence: 99%